Escavação da Mamoa 1 do Alto da Portela do Pau (Castro Laboreiro, Melgaço) -1992 - Jorge, Vítor Oliveira; Silva, Eduardo Jorge Lopes da; Baptista, António Martinho; Jorge, Susana Oliveira (Trabalhos de Antropologia e Etnologia, 2020)
.